Cechy kultury organizacyjnej warunkujące podejmowanie działań pozabiznesowych - Olszewska, Monika (Annales. Etyka w Życiu Gospodarczym, 2014)
Adam Noga, in his review of the theory of entrepreneurship, distinguishes 24 different types of goals which make entrepreneurs establish, run and develop their enterprises. He emphasizes that the maximization of profits, sales volume, satisfactory profits, flow and value were the goals enterprises strived for until the 1970’s. However, entrepreneurship, according to Noga, consists of discovering new targets and objectives which accompany the process of enterprise creation and development, including the growth in the usefulness of human, intellectual and social assets. In order to meet such expectations, appropriate social and or-ganizational conditions need to be ensured.One of these essential conditions is a suitable organizational culture, to a large extent depending on the owners and top rank managers, which con-firms that, today, growth is determined by social capital, human capital, man-agement and organizational culture.This subject is important both from the scientific and practical point of view. It shows that when it comes to management, economy lacks knowledge concerning the cultural context, as well as knowledge related to the assessment of social welfare, in which too little attention is paid to the qualitative elements of social and economic development. The aim of this paper is to answer the ques-tion whether an organizational culture which facilitates undertaking non-business activities exists. In order to answer this question, the notions of non-business activities and organizational culture have been defined. Characteristic features of an organizational culture have been presented and the culture which theoretically facilitates undertaking non-business activities has been indicated. In the empirical part, the theoretical assumptions have been verified and an organizational culture which attempts to achieve not only business goals has been identified.